PELATIHAN APLIKASI PEMANTAUAN STATUS GIZI BALITA BERBASIS MOBILE BAGI KADER POSYANDU PERUMAHAN PURI KENCANA SUMBANG - Purwati, Yuli (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2022)
The Posyandu housing Puri Kencana Sumbang has now formed a cadre to carry out monitoring activities for under-five nutrition by weighing. However, due to the Covid-19 pandemic, this activity has not been carried out routinely. The purpose of this community service is to provide solutions to these problems by conducting training on the implementation of the application for monitoring the nutritional status of children and toddlers using mobile applications and website applications. This activity is in the form of providing information on the standards and indicators used in monitoring the nutritional status of toddlers as well as the use of applications used for the process of recording data on the nutritional status of children and toddlers which can be accessed online to Posyandu cadres and residents of Puri Kencana Sumbang housing. The achievements of this community service activity are that 12 participants consisting of representatives of cadres and residents of housing can understand the standards and indicators used in monitoring the nutritional status of toddlers and increase their ability to use the application for monitoring the nutritional status of toddlers, this is indicated participants became aware of the standards for measuring nutritional status and were able to name the measurement indicators. All participants also agreed that the features in the application were easy to use and very useful for monitoring the nutritional status of toddlers.